United Arab Emirates : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper on the United Arab Emirates highlights the achievements in the diversification of the economy and the developments and outlook of the hydrocarbon sector. The political structure of the Federation gives a great deal of independence to the individual Emirates in pursuing an economic strategy based on their respective comparative advantages. Openness to trade, trade facilitation, and a favorable business environment have enhanced non-oil diversification by stimulating trade and trade-related services.